Genetic associations between accumulated productivity, and reproductive and growth traits in Nelore cattle - Grossi, D. A. [UNESP]; Frizzas, O. G. [UNESP]; Paz, C. C. P.; Bezerra, L. A. F.; Lobo, R. B.; Oliveira, J. A. [UNESP]; Munari, D. P. [UNESP] (Elsevier B.V., 2008)
The total meat yield in a beef cattle production cycle is economically very important and depends on the number of calves born per year or birth season, being directly related to reproductive potential. Accumulated Productivity (ACP) is an index that expresses a cow's capacity to give birth regularly at a young age and to wean animals of greater body weight. Using data from cattle participating in the "Program for Genetic Improvement of the Nelore Breed" (PMGRN - Nelore Brasil), bi-trait analyses were performed using the Restricted Maximum Likelihood method based on an ACP animal model and the following traits: age at first calving (AFC), female body weight adjusted for 365 (BW365) and 450 (BW450) days of age, and male scrotal circumference adjusted for 365 (SC365), 450 (SC450), 550 (SC550) and 730 (SC730) days of age. Median estimated ACP heritability was 0.19 and the genetic correlations with AFC, BW365, BW450, SC365, SC450, SC550 and SC730 were 0.33, 0.70, 0.65, 0.08, 0.07, 0.12 and 0.16, respectively. ACP increased and AFC decreased over time, revealing that the selection criteria genetically improved these traits. Selection based on ACP appears to favor the heaviest females at 365 and 450 days of age who showed better reproductive performance as regards AFC. Scrotal circumference was not genetically associated with ACP. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Beef cattle; Genetic correlation; reproductive efficiency; Heritability